Validation of the WHO Hemoglobin Color Scale Method - Leeniyagala Gamaralalage Thamal Darshana; Deepthi Inoka Uluwaduge (Anemia)
This study was carried out to evaluate the diagnostic accuracy of WHO color scale in screening anemia during blood donor selection in Sri Lanka. A comparative cross-sectional study was conducted by the Medical Laboratory Sciences Unit of University of Sri Jayewardenepura in collaboration with National Blood Transfusion Centre, Sri Lanka. A total of 100 subjects participated in this study. Hemoglobin value of each participant was analyzed by both WHO color scale method and cyanmethemoglobin method. Bland-Altman plot was used to determine the agreement between the two methods. Sensitivity, specificity, predictive values, false positive, and negative rates were calculated. The sensitivity of the WHO color scale was very low. The highest sensitivity observed was 55.55% in hemoglobin concentrations >13.1 g/dL and the lowest was 28.57% in hemoglobin concentrations between 7.1 and 9.0 g/dL. The mean difference between the WHO color scale and the cyanmethemoglobin method was 0.2 g/dL (95% confidence interval; 3.2 g/dL above and 2.8 g/dL below). Even though the WHO color scale is an inexpensive and portable method for field studies, from the overall results in this study it is concluded that WHO color scale is an inaccurate method to screen anemia during blood donations.